Identity, Territory and Modernity. Reflections to Understand Social-cultural Spaces (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This article presents different theoretical and conceptual basis necessary to understand the concept of identity.  This sets forth an analysis of the identity processes and path in a Chilean and Latin American Social historical and cultural context.  Its purpose is to break the opposition between essentialism and modernity.  The construction of identity adults certain mechanisms in the context of a recent modernity.  It also presents a proposal to rescue the subjectivity from subject actions in a social space.  signs of identity the loss in Chile and an explanatory hypothesis from historical discontinuity or analyzed.
Keywords: Identity; Modernity in Latin America; Territorial Identity; Identity Loss; Subject